Avaliação de políticas públicas no financiamento da educação: o Programa de Autonomia Escolar (PAE) na EMEIEF Governador César Cals de Oliveira Filho, Maracanaú – CE - Gonzaga, Maria do Socorro de Melo (2024)
This text analyzes and evaluates the educational financing policy, at the municipal level, whose thematic is the financing of education: School Autonomy Program (PAE) in EMEIEF Governador César Cals de Oliveira Filho, at Maracanaú-CE. Documentary and bibliographical research was used to carry out a brief history of how Brazilian education and educational financing developed, highlighting in each period the economic, political and social conditions of the time, giving a brief report of these policies, seeking to highlight the relationship between educational financing policies and democracy, presentation of the financial decentralization process as a promoter of social inclusion and presentation of the PAE in the social context in which this policy is inserted and its effects on strengthening democratic management, increasing pedagogical, administrative and school finances, in favor of quality education. In the methodology that was used in the search to respond to the proposed objectives, qualitative research was chosen, from the perspective of an in-depth evaluation, with a case study of the research and data collection instruments. This dissertation sought to understand the social, cultural, economic and political facts that influence policy, promoting an approximation with the object of study, promoters or not of a social inclusion of the subjects involved in decision-making and improving the quality of education.